2008
DOI: 10.1002/ibd.20417
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and ecological studies of inflammatory bowel disease in southeastern Norway in 1990–1993

Abstract: The geographic distribution of cases with IBD is not uniformly distributed and is related to urbanization, level of education, and moving pattern. Geographic distribution may be explained by either changes in environment-host relationships or neurobiological mechanisms due to stress and economic frustration. These factors and genetic predisposition might also explain increased familial clustering. Spatial clustering was significant neither for Crohn's disease CD nor ulcerative colitis (UC) but showed a stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
(35 reference statements)
1
22
0
1
Order By: Relevance
“…Previous studies reported higher incidence rates of IBD in urban and periurban areas. 15,17 In contrast, Aamodt et al 39 found that municipalities with a lower tendency toward urbanization had higher incidence rates of IBD. Our study area (northern France) is characterized by the association, in the same region, of rural, periurban, and urban areas, and is very different from the Manitoba region.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported higher incidence rates of IBD in urban and periurban areas. 15,17 In contrast, Aamodt et al 39 found that municipalities with a lower tendency toward urbanization had higher incidence rates of IBD. Our study area (northern France) is characterized by the association, in the same region, of rural, periurban, and urban areas, and is very different from the Manitoba region.…”
Section: Discussionmentioning
confidence: 92%
“…Differences in water supply would also be worth investigating, as a recent study in Norway. 39 Aamodt et al 39 investigated, in a populationbased study, associations between the content and quality of drinking water and the incidence of IBD. The lower CD incidence rates in Seine-Maritime does not necessarily support the hypothesis of Mycobacterium paratuberculosis as an etiologic factor in CD, 40,41 since these bacteria are found in the gut and feces of domestic livestock.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with most epidemiologic studies. 9,[20][21][22][23][24] On the other hand, the EPIMAD registry found that in northern France the CD incidence is higher in rural and periurban areas. 19 However, in the EPIMAD study the highest (Somme) but also the lowest (Seine-Maritime) incidences of CD were rural and periurban.…”
Section: Discussionmentioning
confidence: 99%
“…A disturbed barrier function can lead to the development of such diseases as an intestinal hypersensistivity [46], an irritable bowel syndrome [47,48] and IBD [9] which includes among others Ulcerative colitis (UC) [49,50] and CD [51,52].…”
Section: Paracellular Pathwaysmentioning
confidence: 99%
“…People concentrate more on their careers and work [47], the breastfeeding period is getting shorter [80], there appeared improved domestic conditions with better sanitation and less crowded environment [81], people are exposed to pollution and take to western diet of high amounts of sugar and polysaturated fats [82] as well as to increased tobacco use [83,84,85].…”
Section: Environmental Factorsmentioning
confidence: 99%